The Comfort of the Mystics - Atif Khalil (International Institute of Islamic Thought, 2014)
The early period of Sufism still remains insufficiently explored within western scholarship. Despite the contributions of a range of academic authorities over the past two centuries, stretching back to the publication of Lt. Graham’s 1819 essay, “A Treatise on Sufism, or Mahomedan Mysticism,” followed by the first major European study of the subject two years later by the young Friedrich A. Tholuck, Ssufismus, sive Theosophia Persarum Pantheistica (Sufism, or the Pantheistic Theosophy of the Persians), there still remains a great deal of work to be done in order to better understand the complex, embryonic stages of the Islamic mystical tradition. In this light, The Comfort of the Mystics is a welcome contribution to our growing but still inadequate knowledge of the first few centuries of taṣawwuf. The present work is a critical edition of Abu Khalaf al-Tabari’s (d. 1077) Salwat al-‘Ārifīn wa Uns al-Mushtāqīn (The Comfort of Those Knowing God and the Intimacy of Those Longing for God), a Sufi manual authored in the middle of the eleventh century, shortly after Qushayri’s (d. 1072) famous Risālah. Gerhard Böwering and Bilal Orfali are to be credited with publishing the Salwat for the first time through a close study of the Cairo manuscript (MS Tal‘at Tasawwuf 1553) which was transcribed a decade before Qushayri’s death. While they were unable to access the only other existing manuscript of the entire version of the Salwat, located in Iraq, due no doubt to the political instability of the region and the post-war destruction of the country’s infrastructure, they did manage to compare the work against two later abridged versions. Along with the text, they provide a meticulously referenced introduction which situates the treatise within its broader historical and religious context. The Arabic text is also accompanied by exhaustive indices (127 pages) for Qur’anic verses, hadiths, key figures, locations, technical terms and poetic verses which will be of particular use for researchers. With respect to the author of this little known work, Böwering and Orfali note that the primary sources do not provide us with a great deal of information about his life. On the basis of a well-researched analysis of the medieval source material, they conclude that Tabari was known for his contributions not to the field of Sufism but Shafi‘i law, having studied under some of the leading representatives of the school, including ‘Abd al-Qahir al-Baghdadi (d. 1038), well known for his Al-Farq Bayn al-Firaq, a heresiological survey ...